PENGARUH KOMUNIKASI, KARAKTERISTIK SUPLIER, DAN KUALITAS KERJASAMA TERHADAP KINERJA RANTAI SUPLAI (Studi Kasus pada Proses Produksi PT. Windika Utama, Semarang) - Dwi Anggoro Ramadhan; Sudharto P Hadi; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
A very tight competition requires business managers to create new models in themanagement of the flow of products and information. Because of the presence of the smoothsupply of raw materials Windika Utama PT Semarang can maximize the production process sothat the volume of products sold can be increased. In practice, the supply chain is stronglyinfluenced by suppliers. With the existence of other companies that affect the production processhas become a liability Windika Utama PT Semarang to establish a qualified cooperation.Communication is seen as the most important element for the success of the relationship betweencompanies due to the proven fact that the relationship between the companies always involvescommunication. With the existence of different suppliers means companies need to makeadjustments in the field because every supplier certainly have different characteristics such as howto communicate, the ability of the supplier itself, and the quality of the raw materials areproduced. The quality of good cooperation between the company and suppliers will also have animpact on production processes in the company. This study was followed by analysis to know isthere any influence of communication, the characteristics of the company, and the quality ofcooperation on the performance of the supply chain. This research is a quantitative research with102 respondents in the sample supplier companies in West Java, Central Java and East Java.Data collecting conducted by questionnaire and interview methods. Using the coefficient ofdetermination analysis, multiple regression, and Sobel test performs data processing. Results ofthe study obtained is the relationship of communication variables to variable performance of thesupply chain through the variable quality of the partnership is a relationship of completemediation because that affects the variable performance of the supply chain only variable jobsatisfaction as mediating variables while the relationship between variable characteristicssupplier to variable performance of the supply chain through the variable quality cooperation ispartially mediated the relationship this is due to the occurrence of a significant relationshipbetween the variables of the supplier of the performance characteristics of the supply chain aswell as a significant correlation between the quality of cooperation on the performance of thesupply chain. Advice given to PT Windika Utama Semarang to improve supply chain performanceis to establish good communication with suppliers.